2015
DOI: 10.1002/jps.24132
|View full text |Cite
|
Sign up to set email alerts
|

Stability Analysis of an Inline Peptide-based Conjugate for Metal Delivery: Nickel(II)-claMP Tag Epidermal Growth Factor as a Model System

Abstract: Metals are a key component of many diagnostic imaging and biotechnology applications, and the majority of cancer patients receive a platinum-based drug as part of their treatment. Significant effort has been devoted to developing tight binding synthetic chelators to enable effective targeted delivery of metal-based conjugates, with most successes involving lanthanides rather than transition metals for diagnostic imaging. Chemical conjugation modifies the protein’s properties and generates a heterogeneous mixtu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2016
2016
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…The cla MP Tag is an extremely stable, inline module for targeted metal delivery. 27,30 It consists of the amino acid sequence Asn-Cys-Cys and rapidly and quantitatively binds metal at basic pH, 30,31 here during purification upon exposure to the Ni-IMAC resin. The recognition sequence of Factor Xa follows this cla MP-link spacer in the cla MP-link-MMP-8 construct to permit cleavage of the additional tag and release of the same MMP-8 product.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The cla MP Tag is an extremely stable, inline module for targeted metal delivery. 27,30 It consists of the amino acid sequence Asn-Cys-Cys and rapidly and quantitatively binds metal at basic pH, 30,31 here during purification upon exposure to the Ni-IMAC resin. The recognition sequence of Factor Xa follows this cla MP-link spacer in the cla MP-link-MMP-8 construct to permit cleavage of the additional tag and release of the same MMP-8 product.…”
Section: Resultsmentioning
confidence: 99%
“…The cla MP Tag binds metal extraordinarily tightly at basic pH and this fusion system becomes occupied with nickel during IMAC purification. 30 The metal-free cla MP Tag has been shown to inhibit MMP-8 activity and is being investigated as a potential regulator of the activity of MMP-8. 29 cla MP-link-MMP-8 was originally designed to contain a linker peptide sequence that would allow the cla MP Tag to interact with the active site zinc to potentially inhibit the activity of the enzyme as a pro-moiety that is releasable by adjusting the pH to below neutral or by inserting another metal into the tag.…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies, it was determined that the MAP chemistry is compatible with recombinant production of difficult to express proteins having intramolecular disulfide bonds because the engineered claMP Tag does not interfere with proper folding and protein structure (Mills et al, 2014;Mills and Laurence, 2015). In the preparation of proteins used in these studies, however, slow or incomplete cleavage of the fusion partners was observed for some constructs.…”
Section: Discussionmentioning
confidence: 99%
“…Our lab discovered the unique metal abstraction peptide (MAP) chemistry and developed the inline claMP Tag, which is currently being investigated as a targeted delivery method of transition metals for therapeutic and diagnostic applications. The tag consists of the amino acid sequence Asn-Cys-Cys and binds transition metals extraordinarily tightly (Laurence et al, 2012;Mills et al, 2014;Mills and Laurence, 2015), making it possible to increase effective circulation time and target-specific tissue accumulation for transition metal-based imaging agents. The metal-claMP complex has been shown to not disrupt the overall protein structure, including proteins that depend on formation of multiple, complex disulfide bonds for proper folding and function (Mills et al, 2014;Mills and Laurence, 2015).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation